Design and Development of Milling Fixture for Friction Stir Welding. (2018) - Vijaya Ramnath, B.; Elanchezhian, C.; Rajesh, S.; Jaya Prakash, S.; Kumaar, B. Manoj; Rajeshkannan, K.
Abstract: Friction-Stir Welding (FSW) is a solid-state process for joining of two plates in which there is a relative motion between the tool and work piece, which produces the heat required that makes the material of the two edges to join by atomic diffusion. Friction- Stir Welding of Stainless Steel, Aluminium and various other alloys are done on retrofitted Vertical Milling Machines. For this Friction-Stir Welding operation to occur in a Milling Machine, a milling fixture is required on which the plates which are to be butt welded is fastened. In this paper, we developed a milling fixture and its clamping setup for a Vertical Milling Machine in which Friction-Stir Welding operations are to occur. The fixture was designed with required specifications. The screw clamps are designed in such a way to hold the work pieces rigidly during Friction-Stir Welding operation. Taking into account the lateral and transverse movement of the tool and work piece. Later, the testing of the fixture is carried out by the use of ANSYS Software. The fixture is designed and analyzed for three different materials. The materials analyzed are Cast Iron (C45), Die Steel (D4) and Tool Steel and Hard Alloy (H20). After analyzing, the better material can be used for Friction-Stir Welding operations.